DESCRIPTION OF SUBJECTIVE WELL-BEING AMONG ADOLESCENTS AT AISYIYAH KOTTABARAT ORPHANAGE FOR GIRLS - Agustina, Mutmainah Wulan; Purnomosidi, Faqih; Musslifah, Anniez Rachmawati (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
Living in an orphanage is often perceived as a limitation for adolescents in achieving psychological well-being. However, this study aims to uncover how adolescents living in an orphanage are still able to experience happiness, gratitude, and self-acceptance. This study used a qualitative approach with a case study method. Data were obtained through in-depth interviews, observation, and documentation of several adolescents living in the orphanage. Data analysis was conducted using an interactive model that included data reduction, data presentation, and conclusion drawing. The results showed that adolescents living in an orphanage were able to build subjective well-being through gratitude for their circumstances. They viewed being in an orphanage as not an obstacle to happiness, but rather an opportunity to strengthen themselves. This gratitude was evident in their ability to accept themselves, interpret life experiences positively, and appreciate personal achievements, both small and large. Furthermore, social interactions in the orphanage enriched their experience in understanding the dynamic way life works. In conclusion, despite the limitations of living in an orphanage, adolescents were able to cultivate well-being through self-acceptance, gratitude, and adaptive coping strategies. This shows the importance of providing a conducive environment so that adolescents in orphanages can continue to develop their potential and achieve a prosperous life.